Implikasi Dharma Wacana Terhadap Umat Hindu Di Desa Balirejo Kecamatan Angkona Kabupaten Luwu Timur - Gede Agus Siswadi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
Impact simply can be interpreted as influence or effect. In every decision taken by each individual or group, both positive and negative impacts. Dharma Wacana is a method of religious lectures that can be given by Hindu scholars to improve and broaden the insight of Hindus about their religion. The impact of the implementation of dharma wacana in Balirejo Village is: increasing the understanding of sraddha, applying the concepts and teachings of Hinduism in daily life, and uniting the differences in perceptions of Hindus brought from their home regions in carrying out religious rituals in Balirejo Village.